2019
DOI: 10.1002/jbm.a.36624
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐light‐responsive antibacterial activity of Au‐incorporated TiO2 layers formed on Ti–(0–10)at%Au alloys by air oxidation

Abstract: Rutile TiO2 layers were formed on substrates of Ti–(0–10)at%Au alloys by a simple process of air oxidation, and their antibacterial activities were evaluated under visible‐light irradiation (λ ≥ 400 nm). Au was introduced into the TiO2 layers on Ti–(1–10)at%Au alloys and existed as both metallic Au nanoparticles and dissolved Au3+ ions. The TiO2 layers that formed on Ti–5at%Au and Ti–10at%Au alloys exhibited visible‐light photocatalytic activity, that is, degradation of stearic acid and antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…There have been many reports of additive doping to extend the limited photocatalytic effect of titania in the ultraviolet to visible light region [12,[15][16][17]. Especially, the combination of noble metals (gold or platinum, Au or Pt, respectively), which have excellent biological compatibility, and TiO 2 has been reported to show remarkable visible light photocatalytic activity [18][19][20][21][22]. In previous studies, we found four major absorbance peaks in the ultraviolet (UV), visible, and near infrared (NIR) regions and evaluated the visible-NIR laser-mediated release of antibacterial agent and the accompanying antibacterial activity of Au-coated TiO 2 nanotubes (NTs) [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports of additive doping to extend the limited photocatalytic effect of titania in the ultraviolet to visible light region [12,[15][16][17]. Especially, the combination of noble metals (gold or platinum, Au or Pt, respectively), which have excellent biological compatibility, and TiO 2 has been reported to show remarkable visible light photocatalytic activity [18][19][20][21][22]. In previous studies, we found four major absorbance peaks in the ultraviolet (UV), visible, and near infrared (NIR) regions and evaluated the visible-NIR laser-mediated release of antibacterial agent and the accompanying antibacterial activity of Au-coated TiO 2 nanotubes (NTs) [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Following the removal of duplicates and of irrelevant articles based on the title and abstract, a total of 29 publications were subjected to full-text review. As can be seen in Figure 1 , 20 articles were excluded due to the following reasons: 8 articles were excluded on the basis of their design ( 2 - 4 , 6 , 7 , 13 - 18 ), three due to the impossibility of full-text access ( 19 , 20 ), 5 because they did not investigate air and surface disinfection methods ( 1 , 21 - 25 ), and one because of the impossibility of accessing the results of the randomized clinical trial ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we constructed a PPS by integrating a needle array corona discharge with a highly active Au/TiO 2 plasmonic nanocatalyst [26][27][28], and employed the PPS in the sterilization of the typical microorganism E. coli (ATCC 25922). It was demonstrated that the PPS can improve sterilization efficiency and suppress the generation of secondary pollutants relative to the corona discharge.…”
Section: Introductionmentioning
confidence: 99%